Using Ecological Knowledge and Molecular Tools to Develop Effective and Safe Biocontrol Strategies - Köberl, Martina; Ramadan, Elshahat M.; Roßmann, Bettina; Staver, Charles; Fürnkranz, Michael; Lukesch, Birgit; Grube, Martin; Berg, Gabriele (IntechOpen, 2011)
None